The effect of bright white light therapy and sleep hygiene education on sleep and mental health in adolescents. - Helgi Þór Harðarson 1975- (2021)
Sleep problems in adolescence affect mental health and propose a serious mental health issue. Some sleep problems are due to disruption in the circadian rhythms and or lack of knowledge about sleep hygiene. Therefore, the present study examined if bright white light therapy (BWL), known to entrain circadian rhythms, sleep hygiene education (SE), and the combination of BWL and SE would improve sleep and reduce anxiety and depression. The sample consisted of 65 (48% male, 52% female), 10th-grade students in four classes in two compulsory schools in the capital area of Iceland. Participants in the light groups received either glasses with circadian stimulating Bright White Light (BWL) or glasses with non-circadian stimulating Dim White Light (DWL). Participants in SE groups watched a single 30-minute video about how to adopt healthy sleep behaviors. Classes were randomized to four conditions: (i) BWL plus SE, (ii) BWL minus SE, (iii) Dim White Light (DWL) plus SE, (iv) DWL minus SE. Participants wore glasses for 13 consecutive school days. Participants completed measures of depression, anxiety, and sleep at baseline before the intervention and at the completion of the three-week intervention. Girls reported significantly more depressive symptoms and anxiety symptoms and worse sleep quality. Results from GLM controlling for baseline showed that the main effect for the intervention group was marginally significant for anxiety (p=.08) while it was not significant for depression (p=.22) or sleep (p=.20). However, exploratory comparison between the least squared means at follow-up (controlling for baseline) showed that the BWL+SE group had significantly lower anxiety (p=.01) and depression (P=.04) and marginally better sleep (p=.06) than the DWL-SE. While these trends or results are promising they need to be interpreted with caution until further studies have been conducted with a larger sample, more diverse schools, and long-term follow-up. Keywords: Bright light therapy; Sleep hygiene education; Randomised control ...